Analysis of Social Distancing Variables to Prevention of Positive Cases of Covid-19 Using Path Analysis Method - Atikno, Welly; Kurnia, Hibarkah; Indra Setiawan; Setiawan, Bambang; Nugroho, Bayu Hari; Wahid, Muhammad (TALENTA Publisher, 2022)
Prevention of Covid-19 is important for research in order to reduce positive cases that occur in Indonesia. One of the popular research is using analytical method. The purpose of this study was to determine the relationship between work activity behavior, government and community regulations and social distancing as a mediator in preventing an increase in Covid-19 cases in West Java. This research method uses path analysis model. Social distancing variables directly have a positive and significant impact on preventing positive cases of Covid-19, meaning that with social distancing the spread of the Covid-19 virus can be reduced. The effect of social distancing on the prevention of positive cases of Covid-19 is 87% and the remaining 13% is due to the influence of other factors. Based on the four variables used as predictors of the prevention of Covid-19 cases, the social distance variable is the strongest variable that affects the prevention of positive cases of Covid-19 compared to the other three variables. Social distancing is very important to reduce the spread of Covid-19 cases. The implication of this research shows that awareness of people's behavior by keeping a distance is very important to prevent the Covid-19 virus.